1986
DOI: 10.1128/aem.52.4.824-831.1986
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Vibrio cholerae in hot foods

Abstract: Four food types held hot at 45 to 60°C were deliberately contaminated with 01 and non-Ol Vibrio cholerae strains. These organisms were assayed for survival and recovery from the foods within 1 h of the time the food was kept hot. The results showed no growth of V. cholerae non-Ol on thiosulfate-citrate bile-sucrose agar plates after 24 h of incubation at 37°C for food held hot at 50 to 60°C. Growth was low for V. cholerae 01 and was not achieved in some instances in which foods were held at either 55 or 60°C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Thereis invariably evidence of improper cooking and handling when cooked foods, such as seafood or shellfish, are associated with food poisoning outbreaks due to pathogenic Vibrio species. Cooking foods to achieve internal temperatures above 60°C for several minutes appears satisfactory for eradication of pathogenic vibrios (Boutin, Bradshaw & Stroup, 1982;Shultz et al 1984;Saxena & Kulshrestha, 1985;Makukutu & Guthrie, 1986). Cold smoking of seafood is unlikely to be adequate to remove pathogenic vibrios (Karunasagar et al 1986).…”
Section: Consumption Of Contaminated Foodstuffsmentioning
confidence: 99%
“…Thereis invariably evidence of improper cooking and handling when cooked foods, such as seafood or shellfish, are associated with food poisoning outbreaks due to pathogenic Vibrio species. Cooking foods to achieve internal temperatures above 60°C for several minutes appears satisfactory for eradication of pathogenic vibrios (Boutin, Bradshaw & Stroup, 1982;Shultz et al 1984;Saxena & Kulshrestha, 1985;Makukutu & Guthrie, 1986). Cold smoking of seafood is unlikely to be adequate to remove pathogenic vibrios (Karunasagar et al 1986).…”
Section: Consumption Of Contaminated Foodstuffsmentioning
confidence: 99%
“…Pelos resultados consignados para os alimentos (Tabela 1), depreende-se uma participação discreta desta via de transmissão, a qual não deve ser negligenciada, considerando a ocorrência em alimentos prontos (arroz e macarrão), provavelmente decorrente da participação de um manipulador assintomático ou do uso de água contaminada. É oportuno salientar as observações de Makukutu & Guthrie (1986), que, ao contaminarem arroz e macarrão prontos com vibrião colérico, verificaram que, após aquecimento por uma hora até 60 o C, ainda foi possível detectar bactérias viáveis.…”
Section: Discussionunclassified
“…Cholera has been grown in the laboratory on cold rice and other foods, and experiments have shown that properly heating food inactivates V. cholerae. 7,8 Investigations of previous cholera outbreaks identified eating seafood, uncooked vegetables, and cold leftover rice as risks. [9][10][11] In Jijiga, an increase in cases coincided with Ramadan.…”
mentioning
confidence: 99%